Talent policies - Skille, E. A.; Stenling, C.; Fahlen, J. (Routledge handbook of talent identification and development in sport, 2017)
During the past decades, sport as a policy domain has emerged on government agendas in a wide range of countries, including: United Kingdom (UK) (Coalter, 2007; Green, 2007a; Houlihan, 2005), Switzerland (Chappelet, 2010), Spain (Puig, Martinez, & Garcia, 2010), the Netherlands (Waardenburg, & van Bottenburg, 2013), Norway (Skille, 2009), Sweden (Fahlen & Stenling, 2015), Venezuela (Lopez de D `Amico, 2012), Japan (Yamamoto, 2012), Iran (Dousti, Goodarzi, Asadi, & Khabiri, 2013), New Zealand (Sam, 2009), and Australia (Hoye & Nicholson, 2009). Recendy, elite sport, elite youth sport, and talent policies have become key policy priorities for both governments and non-governmental organizations (Skille & Houlihan, 2014). But, what is talent policy? Our aim in this chapter is to develop some answers to this question. Many definitions o f`policy` centre on the state. Hill (1997), for example, defines policy as `the product of the exercise of political influence, determining what the State does and setting limits to what it does` (p. 41). Thus, policy refers to both process (`exercise o f political influence`) and outcome (`the product of the exercise`).1 However, the state is not necessarily one unity where everybody agrees, as there may be many views across state politicians or bureaucrats (Houlihan, 1997). Moreover, the state is not the only actor within a policy field (Sabatier & Jenkins-Smith, 1999). This is particularly the case in the sport policy field where non-governmental sport organizations both have a stake in the making of government sport policy and formulate their own policies, including those pertaining to talent identification and development. These policies may be more or less in line with those outlined by the government (Fahlen & Sjoblom, 2012). In that sense, the Oxford Thesaurus of English`s definition of policy as a `course or principle of action adopted or proposed by organization`2 refers to policy as a principle of action set out by any type of organization, not solely governments.